2020
DOI: 10.1002/eap.2225
|View full text |Cite
|
Sign up to set email alerts
|

Smokey the Beaver: beaver‐dammed riparian corridors stay green during wildfire throughout the western United States

Abstract: Beaver dams are gaining popularity as a low-tech, low-cost strategy to build climate resiliency at the landscape scale. They slow and store water that can be accessed by riparian vegetation during dry periods, effectively protecting riparian ecosystems from droughts. Whether or not this protection extends to wildfire has been discussed anecdotally but has not been examined in a scientific context. We used remotely sensed Normalized Difference Vegetation Index (NDVI) data to compare riparian vegetation greennes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 26 publications
0
37
0
Order By: Relevance
“…This study focuses on high flow periods, but it is worth noting that reduced flashiness observed supports research indicating the slowed release of water from leaky dams may maintain or elevate stream baseflows (Nyssen et al, 2011) during dry periods (Majerova et al, 2015; Puttock et al, 2017; Woo & Waddington, 1990). There is a need for further research into baseflow maintenance, with an increase in hydrological extremes predicted globally (Dadson et al, 2017; Larsen et al, 2009; Romanowicz et al, 2016) both attenuating stormflow and maintaining flow and wetness during drought periods (Fairfax & Small, 2018; Gibson et al, 2015) or even fire episodes (Fairfax & Whittle, 2020) which could have major ecological and societal benefits.…”
Section: Discussionmentioning
confidence: 99%
“…This study focuses on high flow periods, but it is worth noting that reduced flashiness observed supports research indicating the slowed release of water from leaky dams may maintain or elevate stream baseflows (Nyssen et al, 2011) during dry periods (Majerova et al, 2015; Puttock et al, 2017; Woo & Waddington, 1990). There is a need for further research into baseflow maintenance, with an increase in hydrological extremes predicted globally (Dadson et al, 2017; Larsen et al, 2009; Romanowicz et al, 2016) both attenuating stormflow and maintaining flow and wetness during drought periods (Fairfax & Small, 2018; Gibson et al, 2015) or even fire episodes (Fairfax & Whittle, 2020) which could have major ecological and societal benefits.…”
Section: Discussionmentioning
confidence: 99%
“…In a fully functional river-wetland corridor, this intrinsic, geomorphic resilience to disturbance is further enhanced by riverine biota. Beaver modifications of the river corridor increase resilience to drought (Hood and Bayley, 2008) and wildfire (Fairfax and Whittle, 2020). The dense vegetation of river-wetland corridors can enhance the resistance of these systems to flood-induced erosion and deposition (Heffernan, 2008).…”
Section: Interactions and Feedbacksmentioning
confidence: 99%
“…Resilience is the persistence of relationships within a system and is a measure of the ability of the system to absorb changes of state and driving variables (Holling, 1973). River-wetland corridors are generally more resistant to drought and wildfire because of the elevated water table and relative abundance of standing water (e.g., Hood and Bayley, 2008;Fairfax and Whittle, 2020). Sediment pulses that can severely damage dysfunctional channels in the aftermath of wildfire are instead distributed and attenuated across functional river-wetland corridors, resulting in less significant impacts.…”
Section: Significancementioning
confidence: 99%
“…This in turn can increase the duration of the rising limb of the flood hydrograph which can reduce the peak discharge of floods (Burns & McDonnell, 1998; Green & Westbrook, 2009; Nyssen, Pontzeele, & Billi, 2011). Additionally, water stored in beaver ponds is released slowly as the porous dams gently leak both during and following rainfall, elevating stream base flows even during prolonged dry periods (Majerova, Neilson, Schmadel, Wheaton, & Snow, 2015; Puttock et al, 2017; Woo & Waddington, 1990), increasing environmental resilience to risks including drought and fire (Fairfax & Whittle, 2020).…”
Section: Beaver Impact Upon the Environment—contemporary Understandingmentioning
confidence: 99%